In-situ grown ternary metal hydroxides@3D oriented crumpled V₂C MXene sheets for improved electrocatalytic oxygen evolution reaction - Iqbal, Anum (2024)
High valence multi transition metal hydroxides are greatly enriched with OER redox active sites due to strong synergy of heteroatomic nuclei. The efficiency of these redox active sites could be efficiently improved by coupling with highly conductive substrate. The advanced three-dimensional (3D) architecture and hydrophilic terminal functionalities of MXene (MX) considerably enhance the maximum utilization rate of anchored redox active sites by triggering the direct growth of these at MX substrate. Here-in, the freeze-dried 3D network of crumpled Vanadium-Carbide (V₂C) MX sheets regulates the crystallization of in-situ grown NiFeCr multi transition metal hydroxides on MX scaffold through co-precipitation process. The XPS results suggest a synergistic chemical interaction of 3D MX scaffold with NiFeCr that modifies the electronic structure of the composite ensuring reduced charge transfer resistance. Besides, as found in FESEM morphological investigation, the well-dispersed NiFeCr multi-transition metal hydroxides are immobilized on open pores like structure of V₂C-MX facilitate thoroughly accessible active sites. As a result, the NiFeCr@3D V₂C-MX composite has shown an excellent electrocatalytic activity with an overpotential of 410 mV at a current density of 200 mA cm⁻², Tafel slope of 100 mV dec in 1M KOH. Besides, the significant interaction between metallic centers and MXene support prevent detachment or agglomeration of active centers providing maximum interaction with the electrolytic ions, quick ionic OH⁻ transportation, speedy and stable electron transfer channels thus ensure the long-term stability of NV-5MX during 53 h continuous operation of OER. Furthermore, we have utilized a more accurate value of half-cell standard reduction potential of the Hg/HgO electrode in the Nernst equation to represent all test voltages and to determine the overpotential values. In essence, this study features a facile approach for the confined growth of multi transition metal hydroxides in the presence of morphologically unique 3D crumpled V₂C MXene architectures. Consequently, the increased OER reaction kinetics and improved stability of the synthesized composites are potentially due to synergistic interplay between well dispersed active sites and the conductive substrate.